Kerangka Konseptual Optimalisasi Pengendalian Persediaan pada Produk Perishable - Alfarisi, Salman; Ardiansyah, Arif (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Inventory management is a critical component of the retail industry, particularly in the context of perishable products. The objective of this study is to propose a conceptual framework for the selection of inventory control strategies, with the aim of enhancing cost efficiency for perishable products with limited lifetime. In this study, we first analyze the inventory control of perishable products according to sales levels data using the ABC classification method. Subsequently, demand patterns are identified to determine the inventory method to be used. This study identifies the potential of the Periodic Review System to determine the optimal order quantity, thereby enhancing cost efficiency. This study utilizes the fruit retail sector as a case study to implement the proposed conceptual framework. The findings indicate that the Periodic Review System has the potential to minimize total inventory expenses in comparison with the existing conventional method.